Masked Delivery of Allergen in Nanoparticles Safely Attenuates Anaphylactic Response in Murine Models of Peanut Allergy - Hughes, Kevin R.; Saunders, Michael N.; Landers, Jeffrey J.; Janczak, Katarzyna W.; Turkistani, Hamza; Rad, Laila M.; Miller, Stephen D.; Podojil, Joseph R.; Shea, Lonnie D.; O'Konek, Jessica J. (Frontiers in Allergy, 2022)
Food allergy is a growing health concern worldwide. Current allergen-specific immunotherapy (AIT) approaches require frequent dosing over extended periods of time and may induce anaphylaxis due to allergen-effector cell interactions. A critical need remains to develop novel approaches that refine AIT for the treatment of food allergies. Previous studies show that poly(lactide-co-glycolide) (PLG) nanoscale particles (NP) effectively suppress Th1- and Th17-driven immune pathologies. However, their ability to suppress the distinct Th2-polarized immune responses driving food allergy are unknown. Herein, we describe the safety and efficacy of NPs containing encapsulated peanut allergen in desensitizing murine models of peanut allergy. Peanut extract encapsulation allowed for the safe intravenous delivery of allergen relative to non-encapsulated approaches. Application of 2–3 doses, without the need for dose escalation, was sufficient to achieve prophylactic and therapeutic efficacy, which correlated with suppression of Th2-mediated disease and reduced mast cell degranulation. Efficacy was associated with strong reductions in a broad panel of Th1, Th2, and Th17 cytokines. These results demonstrate the ability of PLG NPs to suppress allergen-specific immune responses to induce a more tolerogenic phenotype, conferring protection from intragastric allergen challenge. These promising studies represent a step forward in the development of improved immunotherapies for food allergy.